Nanoimprint lithography-based replication techniques for fabrication of metal and polymer biomimetic nanostructures for biosensor surface functionalization. (16th April 2023) - Nowduri, Bharat; Britz-Grell, Anette; Saumer, Monika; Decker, Dominique
Abstract: Nanostructuring is a promising and successful approach to tailor functional layers and to improve the characteristics of biosensors such as signal transmission and tighter cell-surface coupling. One of the major objectives in biosensing and tissue engineering is the development of interfaces that mimic the natural environment of biosystems composed of extracellular matrix biomolecules. Nevertheless, effective techniques to reconstruct the random distribution of these biomolecules are still not well established. For this reason, the presented work demonstrates different methods based on nanoimprint lithography to replicate randomly distributed natural nanostructures with complex geometries into different polymers and metals. The fidelity of the replicated nanostructures has been evaluated by atomic force microscopy and the attributes of the fabrication processes have been discussed. Finally, different replication techniques have been combined for the biomimetic nanostructuring of the dielectric passivation layer as well the metal electrode surface to develop novel whole-surface-nanostructured microelectrode arrays.